THE INFLUENCE OF CAREER DEVELOPMENT AND COMPENSATION ON WORK SATISFACTION AND ITS IMPLICATIONS AGAINST TURNOVER INTENTION AT AJB BUMIPUTERA 1912'S HEAD OFFICE - Didik Sulistiyono; Muhammad Havidz Aima (Dinasti Publisher, 2020)
This research aims to discovered those influence of career development and compensation towards turnover intention that mediated through work satisfaction. The research object were the employees of AJB Bumiputera 1912's head office. As many as 177 respondents filled these questionnaire, and sample was taken by Slovin formula from total population of 317 employees. This research was conducted in October 2019 until April 2020 at AJB Bumiputera 1912's head office. The sampling technique used proportional stratified random sampling while data were analyzed by SmartPLS (Partial Least Square)of path analysis application. The results from this research were indicated that career development had no significant influence on Turnover Intention and compensation had positive and significant impact towards turnover intention. Meanwhile, work satisfaction became a mediate factor between career development and compensation to turnover intention. Work satisfaction could mediated career development perfectly. And work satisfaction only had partial impact towards compensation.